Factores que influyen en la calidad de vida de las personas con discapacidad, del sector buenos aires centro, en el distrito de Víctor Larco Herrera - Trujillo, Año 2015. - Mariños Melón, Irma Bertila (2016)
This thesis was conducted in order to investigate the factors that influence the quality of life of people with disabilities, the District of Victor Larco Herrera, industry Buenos Aires Center, 2015. That's why it was considered a type of applied research, based on design description. For them he had a sample of 47 people with disabilities Buenos Aires Industry Center, Victor Larco Herrera district. The aim was to describe the (physical, emotional and family) factors influencing the quality of life of people with disabilities For which a quantitative and qualitative methodology was applied, using the instruments: Survey on the (physical, emotional and family) factors and guide depth interview that allowed to obtain the testimony of their life experiences of family and people with disabilities. Through this investigation it concludes that the physical, family and emotional factors influence the quality of life of people with disabilities, as they are vital piece for the development, and development of the person.